The transparency and p-type performance in B6P: The hybrid functional study. (1st January 2023) - Chen, Yu; Yang, L.; Wang, Z.L.; Fan, S.W.
Abstract: The transparency and p-type performance for B6 P is investigated by the hybrid functional calculations. It is found that B6 P is an indirect band gap semiconductor with a band gap of 3.23 eV. The hole effective mass along the T to Γ direction is only 0.35 m 0, where m 0 is the mass of the free electron. The B6 P is a promising high transparent material due to its low absorption, low reflection, and high transmittance. For intrinsic B6 P, BP (PB(B) ) is the main defect under B-rich ( P -rich) condition. The formation energy of the dominant defect is calculated. The thermodynamic simulation method is performed to quantitatively study the Fermi energy, hole concentration, and defect density. Our results show that quenching the intrinsic B6 P from 1900 K to room temperature can increase the holes' density from 9.86 × 10 2 to 2.80 × 10 13  cm −3 . These results provide essential insight for B6 P as a potential transparent p-type material. Highlights: B6 P is an indirect band gap semiconductor with the band gap 3.23 eV. Hole effective mass along T-Γ direction is only 0.35 m 0 (m0 is the mass electron). B6 P is high transparency for low absorption and high transmittance. The hole concentration for B6 P with intrinsic defects can reach 2.80 × 10 13  cm −3 .